Estudio taxonómico de cuatro especies de encino (Quercus) descritas por Warburg - Aguilar Enriquez, Ma. de Lourdes; Romero Rangel, Silvia (Instituto de Ecología, A.C., 1995)
Q. apiophylla Warb., Q. ochroestes Warb. and Q. sagata Warb. were determined as synonyms of Q. hintonii Warb. on the basis of analysis of original descriptions, phototypes, and specimens in the herbaria; furthermore, observations of populations and collections of specimens were done in the type localities.